Psychometric characteristics of Turkish version of metacognitions about online gaming scale - Denizci Nazlıgül, Merve; Süsen, Yankı (Journal of Dependence, 2021)
Objective: The purpose of the present study was to assess the psychometric properties of the Turkish version of the Metacognitions about Online Gaming Scale (MOGS-T).Method: Two studies were carried out with samples of video gamers (n1 = 196, n2 = 150) who filled a set of questionnaires including the demographic information form, MOGS-T, Gaming Addiction Scale, Internet Addiction Test, and Depression Anxiety Stress Scales (DASS).Results: MOGS-T had good internal consistency and test-retest reliability. The factor structure of the MOGS-T was examined through exploratory factor analysis in the first study. A two-factor solution with positive metacognitions about online gaming and negative metacognitions about online gaming subscales showed the best fit to the data. A second study was performed to verify the factor structure of the scale and examine the predictive ability of MOGS-T factors. Hierarchical regression analyses demonstrated that positive metacognitions about online gaming significantly predicted weekly online gaming hours, negative metacognitions about online gaming significantly predicted Internet addiction, and both metacognitions about online gaming significantly predicted gaming addiction. Conclusion: MOGS-T has reliable and valid psychometric properties for this population.
Keywords: Üstbiliş; video oyunları; bağımlılık; psikometri